2014
DOI: 10.3389/fpubh.2014.00046
|View full text |Cite
|
Sign up to set email alerts
|

ADHD and Adolescent Athletes

Abstract: Attention-deficit hyperactivity disorder (ADHD) is a common neurodevelopmental disorder that affects the child and adolescent population. It is characterized by impairment in attention/concentration, hyperactivity, and impulsivity, all of which can impact performance of athletes. ADHD treatment within the athletic population is a unique challenge. The research in this field has been relatively limited. The National Collegiate Athletic Association and International Olympic Committee both regulate the use of psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 74 publications
1
13
0
Order By: Relevance
“…These are attributes that in previous studies have been shown to have a positive influence on ADHD symptoms [23,24]. In adolescence, physical activity has been reported to improve the ADHD symptoms in the individual as well as his or her academic performance and the adolescence overall attitude [1,24,25]. It has been shown that physical activity increases levels of dopamine and norepinephrine, which are deficient in ADHD children and adolescents [26].…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…These are attributes that in previous studies have been shown to have a positive influence on ADHD symptoms [23,24]. In adolescence, physical activity has been reported to improve the ADHD symptoms in the individual as well as his or her academic performance and the adolescence overall attitude [1,24,25]. It has been shown that physical activity increases levels of dopamine and norepinephrine, which are deficient in ADHD children and adolescents [26].…”
Section: Introductionmentioning
confidence: 81%
“…Attention deficit hyperactivity disorder (ADHD) is considered a disorder that can cause behavioral and emotional problems for the individual [1]. Studies have shown how the environment, as well as physical activity, can influence ADHD in a positive direction and prevent its negative effects [1,2]. Most ADHD studies focus on the problems the individual has developed due to the disorder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the medication used for ADHD and similar conditions are especially prone to abuse. Literature suggests that the prevalence of ADHD is higher in athletes at both collegiate and professional levels compared to the general population, which might indicate abuse (Nazzer, Mansour & Gross 2014;Reardon 2016). However, reliable scientific literature in this field is scarce.…”
Section: Pharmacological Neuroenhancementmentioning
confidence: 99%
“…Medication and also non medication treatments are available, but studies show that medication has superior results [20].…”
Section: Management Of Adhdmentioning
confidence: 99%